Convergence in West German Regional Unemployment Rates - Falko Juessen; Christian Bayer (European Regional Science Association (ERSA), 2005)
Differences in regional unemployment rates are often used to describe regional economic inequality. This paper asks whether changes in regional unemployment differences in West Germany are persistent over time. Only if such changes are persistent, the differences are a sensible measure of inequality and only then can policies be effective that aim at lowering the dispersion of unemployment rates. Our analysis follows a time-series approach to economic convergence and we test whether unemployment differences between regions are stationary or not. While univariate tests show that changes in unemployment differences are persistent, more powerful panel tests find them to be only transitory. However, these tests reveal only a moderate speed of convergence. Since there is a structural break following the second oil crisis, we also employ unit-root tests that allow for such break. Again we find strong evidence for convergence and now also the speed of convergence is found to be very high. Both results, the presence of regime-wise conditional convergence in regional unemployment rates and fast equilibrium adjustment, have important implications for economic policy targeted at regional unemployment. On the one hand, small government interventions loose their effect quickly as unemployment rates adjust back to their equilibrium levels. On the other hand, large interventions might move the economy from one equilibrium of regional unemployment rates to the other. This means the policy intervention needs to take the form of a substantial regime shift. Most policies that aim at reducing relative unemployment differentials are unlikely to make permanent contributions to social welfare.
Keywords: 330